The Legitimacy of BPI Danantara: Investment Management Responsibility in the Context of Business Judgment Rule - Laksmanajati, Teofilus Dendro; Fachrizal, Fachrizal; Rato, Dominikus; Ohoiwutun, Y.A. Triana (Universitas Internasional Batam, 2025)
The establishment of Danantara as a national investment management institution (sovereign wealth fund) based on Law Number 1 of 2025 is a strategic step in consolidating state-owned enterprises' assets and capital to support economic growth and public welfare. However, the implementation of Danantara faces various legal and governance issues, particularly related to the dual roles of public officials, restrictions on the authority of the Supreme Audit Agency (BPK), and potential structural conflicts of interest that weaken the principles of Good Corporate Governance (GCG). In addition, the regulation of the Business Judgment Rule (BJR) principle in this law poses its own challenges: on the one hand, it protects directors from criminalization of investments, but on the other hand, it has the potential to open loopholes for abuse of authority if it is not balanced with effective oversight mechanisms. This study uses a normative and prescriptive-analytical juridical approach, examining the synchronization of norms in Law 1/2025, Law 40/2007 on Limited Liability Companies, and the practice of applying BJR in BUMNs, such as the Pertamina BMG Block case, the Garuda Indonesia case, and PT PLN Batubara. The results of the study show that the implementation of BJR in BUMNs and Danantara is effective in preventing the criminalization of business decisions if the directors are able to prove the elements of good faith and duty of care. However, there are still weaknesses in the aspects of transparency, accountability, and independence of supervision, which have the potential to reduce public trust. Therefore, it is necessary to strengthen the role of independent audits, prohibit public officials from holding multiple positions, and implement compliance reporting-based supervision to ensure that the BJR principle is carried out in accordance with the corridor of law and business ethics.